aMMP-8 Oral Fluid PoC Test in Relation to Oral and Systemic Diseases - Sorsa, Timo; Nwhator, Solomon Olusegun; Sakellari, Dimitra; Grigoriadis, Andreas; Umeizudike, Kehinde Adesola; Brandt, Ella; Keskin, Mutlu; Tervahartiala, Taina; Pärnänen, Pirjo; Gupta, Shipra; Mohindra, Ritin; Bostanci, Nagihan; et al. (Frontiers in Oral Health, 2022)
The manuscript uses the previously published literature and highlights the benefits of active-matrix metalloproteinase (aMMP)-8 chairside/point-of-care (PoC) diagnostic tools as adjunctive measures in oral and systemic diseases. Previous studies suggest that as a biomarker, aMMP-8 is more precise than total MMP-8, MMP-9, MMP-2, MMP-3, MMP-13, MMP-7, MMP-1, calprotectin, myeloperoxidase (MPO), human neutrophil elastase (HNE), tissue inhibitor of matrix metalloproteinase (TIMP)-1, and bleeding of probing (BOP). Therefore, aMMP-8 could be implemented as the needed key biomarker for the new disease classification for both periodontitis and peri-implantitis. With a sensitivity to the tune of 75–85% and specificity in the range of 80–90%, lateral flow aMMP-8 PoC testing is comparable to catalytic protease activity assays for aMMP-8. The test can be further applied to estimate the glycemic status of an individual, to ascertain whether a person is at risk for COVID-19, in managing the oral side effects of radiotherapy carried in head and neck cancers, and in selected cases pertaining to reproductive health. In the future, aMMP-8 could find application as a potential systemic biomarker in diseases affecting the cardiovascular system, cancers, bacteremia, sepsis, diabetes, obesity, meningitis, as well as pancreatitis. The aMMP-8 PoCT is the first practical test in the emerging new dental clinical field, that is, oral clinical chemistry representing oral medicine, clinical chemistry, peri-implantology, and periodontology.